1999
DOI: 10.1210/jcem.84.1.5366
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Biochemical Phenotype of Familial Anterior Hypopituitarism from Mutation of the PROP1 Gene1

Abstract: We have investigated the largest family with PROP1 deficiency reported to date. Eight patients, aged 17-40 yr, in two sibships with possibly related mothers but no parental consanguinity were 109 -137 cm in height (Ϫ8.8 to [minsu]5.9 SD score) and sexually immature. None had received hormonal therapy. Affected individuals had similarities to and significant differences from patients with insulin-like growth factor I (IGF-I) deficiency due to GH receptor deficiency (GHRD) and normal thyroid function and sexual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…MRI of the pituitary gland in patients with PROP-1 mutations showed either normal findings, a small pituitary gland or an enlargement of the sella turcica with suprasellar extension of a pituitary mass [12, 22, 23, 24, 25]. The different imaging protocols in our patients did not allow volumetric calculation of the anterior pituitary volumes.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…MRI of the pituitary gland in patients with PROP-1 mutations showed either normal findings, a small pituitary gland or an enlargement of the sella turcica with suprasellar extension of a pituitary mass [12, 22, 23, 24, 25]. The different imaging protocols in our patients did not allow volumetric calculation of the anterior pituitary volumes.…”
Section: Discussionmentioning
confidence: 67%
“…Mutations of PROP-1 , a paired-like homeodomain transcription factor, have been recently reported as a cause of CPHD [5, 6, 7, 8, 9, 16]. Patients with these mutations suffer from GH, PRL, TSH, LH and FSH deficiencies [12]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There seems to be no significant difference in the size of the pituitary gland in patients with PIT-1 mutations versus those with PROP-1 mutations [43]. Some authors have reported intra- or parasellar masses leading to sellar enlargement in patients with PROP-1 defects [44, 45]. The nature of these spontaneously regressing masses is still a matter of debate.…”
Section: Factors Affecting Pituitary Organogenesismentioning
confidence: 99%
“…However, there is a great phenotypic variability among patients with PROP1 gene mutations causing CPHD (6,7). Growth hormone deficiency occurs most commonly, but growth retardation can be modest or severe.…”
Section: Introductionmentioning
confidence: 99%